The role of legislation in K-12 school discipline: The silence of action - Bo, Mengmeng; Onwubuya, Gift Chinemerem (Frontiers in Psychology, 2022)
Researchers have consistently identified the disparity between teachers’ practical and legal knowledge regarding teachers’ right to discipline students. However, few studies have investigated teachers’ construction processes that form construction outcomes, which would help navigate the role of legislation in school discipline. This study contributes to a holistic picture of the neglected disciplinary rights that teachers construct in teaching practice and their underexplored attitude towards the law, using an interview-based constructionist method on twelve teachers of Lvliang city in a Chinese K-12 context. The findings suggest that the participants prefer to acquire discipline knowledge by interacting with multiple power relations in their local environment and that their knowledge is historically and culturally specific. Although the disciplinary right they construct is never static, balanced, or essentialised, the participants’ constructions are commonly not in line with legal provisions or the aims of the law. Furthermore, school discipline legislation plays a silent role in empowering teachers to discipline students, but it is more visible in holding back teachers’ use of corporal punishment. These findings illustrate the complexity of implementing school disciplinary law as a universal national policy.